Desentralisasi Fiskal dan Ketimpangan Pendapatan Kabupaten/Kota di Provinsi Jawa Barat - Kharisma, Bayu; Hanifah, Hani (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2020)
Income inequality is one of the problems that must be addressed immediately because it can have an impact on economic inefficiency and weaken the stability of social solidarity. One of the policies that can reduce income inequality is fiscal decentralization implementation. Specifically, this study aimed to analyze the effect of fiscal decentralization on income inequality in regencies and cities in West Java. The model used in this research was a fixed effect panel data regression. Fiscal decentralization was measured by adding the total regional revenue (Pendapatan Asli Daerah/PAD) to revenue sharing (Dana Bagi Hasil /DBH) and divided by the total regency and city expenditure. Income inequality was measured by using the Gini Ratio. The results indicated that fiscal decentralization could reduce income inequality in regencies and cities in West Java. The reason was that, through decentralization, local government could manage their finance and affect the welfare level. In addition, local government could also implement certain policies to increase the potential of each region.